Isolating and Identification germs of Staphylococcus aureus from of butchers' Shops Instrument in the Shekhan District - Al-Saiegh, Abdullah. M.; Mahdi, Raghdah; Meskeen, Sabah; Shreen ftah,; Zedan, Wesam (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the study was conducted to isolation microbial contamination in butchers instruments and meat in shekhan district, and identify the most important bacterial species associated with these instruments. 65 samples were taking from different localities of Shekhan district distributed among (9 samples from kalakchi area, 15 samples from chera area, 21 samples from qasrok area and 20 samples from shekhan) After taken sample by a swab from tools of butcher's shops (Knife ,hooks , cutting board and meat grinder) after that the samples were taken to the laboratory of shekhan technical colleague of health for completion process of culturing, isolated and examined of the bacterial species and studying the morphological biochemical characteristics of bacteria by using culture media. The results of the current study showed growth six different species of bacteria were Staphylococcus aureus 24 samples (36%) Staphylococcus epidermidis 9 samples (14%), Staphylococcus saprophytes 5 samples (8%), Streptococcus 9 samples (14%), Bacilli species 2 sample (3%) , Gram negative species 16 samples (25%) . At the conclusion of this study, two types of bacteria were isolated the first of which was gram negative and its proportion was (25%) the second was gram positive and its proportion was (75%), Identified six species of bacteria was staphylococcus aureus, staphylococcus epidermidis, staphylococcus saprophytous, streptococcus and bacilli species.